Análisis de la motivación del estudiante de educación superior participante en una propuesta de evaluación formativa - Campos-Mesa, M.; González-Campos, G.; Castañeda-Vázquez, C. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
The main aim of this study is to analyze the influence of an educational innovation based on formative assessment, on the motivation of university students towards a subject of the Degree in Primary Education. To this end, 91 students from University of Seville participated in a teaching innovation project during the 2018-2019 academic year, where a general process of formative assessment as well as other didactic and technological resources were applied, such as use of gamification and interactive response commands, among others. At the end of the intervention students answered the Spanish version of Motivated Strategies for Learning Questionnaire (CEAM II) in order to analyze, among other variables, students’ motivation. The findings show high levels of motivation, both intrinsic and extrinsic. Therefore, the data obtained suggest this experience can be considered as a good educational practice and they encourage us to continue working in this line.